2012
DOI: 10.1142/s179398441100044x
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanics of Drug-Treated Leukemia Cells Investigated Using Optical Tweezers

Abstract: Leukemia is a very common cancer worldwide, and different drugs have been applied to treat the disease. However, the influence of the drugs on the biomechanical properties of leukemia cells, which are related to the risk of leukostasis, is still unknown. Moreover, accurate measurement of biomechanical properties of leukemia cells is still a challenging task because of their non-adherent nature and high sensitivity to the surrounding physiological conditions. In this study, a protocol to measure the biomechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Mechanical properties of K562 cells have been previously measured using different techniques. Indentation of optically trapped beads into cells immobilized on a fibronectin-coated glass surface gave a stiffness of 160 Pa (48). AFM measurements of cells trapped in microwells gave stiffness values at~50 Pa (11).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical properties of K562 cells have been previously measured using different techniques. Indentation of optically trapped beads into cells immobilized on a fibronectin-coated glass surface gave a stiffness of 160 Pa (48). AFM measurements of cells trapped in microwells gave stiffness values at~50 Pa (11).…”
Section: Discussionmentioning
confidence: 99%
“…Some cells such as K562, macrophage and/or certain granulocytes do not even need such protein fixing. We have shown that optical tweezers can be used to perform indentation on these cells 20 .…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we demonstrate that the intrinsic elastic moduli of living cells can be extracted by using optical tweezers based on the rate-jump method. In contrast with other methods including atomic force microscopy (AFM), micropipette aspiration and magnetic tweezers, carrying out lateral indentation in an optical tweezers has the merit of allowing the indentation processing to be recorded, thus offering control of the indenter sphere at the desired indentation position with submicron precision [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stimuli are indeed commonly encountered in daily life, including mechanical vibrations, temperature fluctuations, and environmental radiations. Optical tweezers are commonly used to manipulate transparent microbeads to interact with cells (Liang et al, 1996), bacteria (Rasmussen et al, 2008), DNA (Zhuang, 2004), and RNA (Wen et al, 2007), to measure macromolecular interactions (Zhou et al, 2012), to do cell indentation (Zhou et al, 2011), and so forth. In the current study, optical tweezers were used to manipulate single cells mechanically at different frequencies and amplitudes, and their effects on the cells were observed with in situ optical and fluorescent microscopy.…”
mentioning
confidence: 99%